Maintenance Cost Analysis Using Cost of Unreliability (COUR) Method with Business Consequence Analysis : A Case Study of Shot Blast Machine - Jasmine Raisya Salsabila; Fransiskus Tatas Dwi Atmaji; Aji Pamoso (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
Losses caused by unreliable machines in a production line will affect the total cost losses from a manufacturing company's production process. Based on historical data of damage that has been obtained from the maintenance department of XYZ companies, the MACH MWJ 9/10 Shot Blast Machine is the machine that has the highest-level frequency of damage. This machine is useful for cleaning sand or residual production dirt that sticks to workpieces that have been cast in the casting process, especially for E-Clips components. The research's purpose is to determine the value of cost losses due to machine unreliability using the Cost of Unreliability (COUR) method, with Business Consequence analysis (BC) analysis. The cost effects of these costs include Corrective COUR and Downtime COUR. The final calculation of COUR shows that the total cost of COUR Downtime caused by the unreliability of the machine is greater than the total Corrective COUR. After calculating the COUR, an analysis of the business consequences resulting from the machine's unreliability is carried out using a risk matrix. The analysis results show that the shot blast machine's critical components are in the red or high-risk category and have a very high Probability of Failure (PoF). The results of COUR analysis with business consequence analysis will be an input for the company to make a machine maintenance system policy, especially for the MACH MWJ 9/10 Shot Blast machine's critical components. In general, this research's novelty is to combine the application of the Cost of Unreliability method with an analysis of the effects of the Business Consequence caused by the machine's selected critical components.